Energy substrate used by workers of leaf-cutting ants during nest excavation - Camargo,Roberto S. (2013)
Energy substrate used by workers of leaf-cutting ants during nest excavation. In this study we aimed to ascertain whether leaf-cutting ant workers lose body reserves (fat or sugars) as a function of nest excavation. For each treatment, we isolated 10 workers of Atta sexdens into two experimental groups, Control (C- without excavation) and Soil (S- with excavation), which were kept for different time intervals (0, 24, 48 or 72 hours), totaling 700 tested workers. We then determined the concentration of soluble carbohydrates and total lipid content in them. The total carbohydrates were determined colorimetrically, based on the reaction between carbohydrates and sulfuric acid-phenol. For determination of lipids, the insects were immersed in organic solvent until they reached a constant weight. Our results showed that carbohydrates are consumed during nest excavation activities. In the experimental groups S24, S48 and S72, there was an average reduction of 5.82 (20.42%), 14.31 (44.96%) and 13.27 (43.96%) µ.mg-1 in soluble sugar when compared with the experimental groups that did not excavate. Furthermore, the lipids were not used during this activity. With respect to dry mass of the workers, their values were C0 = 8%, C24 = 10.4%, C48 = 9.2%, C72 = 10%, S24 = 9.2%, S48 = 8.7% and S72 = 8.5%. Our results show experimentally that the source of energy for nest excavation is carbohydrates, whereas lipids are conserved for other activities.